Increased serum concentration of apolipoprotein B is associated with an increased risk of reaching renal replacement therapy in patients with diabetic kidney disease - Wen-bo Zhao; Lin Zhu; Tohty Rahman (Renal Failure, 2020)
Objective Few studies have investigated the association of apolipoprotein B (ApoB) with the progression of diabetic kidney disease (DKD) and the risk of renal replacement therapy (RRT). Method In this retrospective cohort study, a group of 258 DKD patients with stage 3–5chronic kidney disease(CKD)were divided into low ApoB (<1.1 g/L) and high ApoB (≥1.1 g/L) groups and followed-up for 20.51 ± 6.11 months. The association of the serum ApoB concentration with RRT was determined by Kaplan–Meier and Cox regression analysis. ApoB was measured in the serum. Results Ninety-three of the 258 DKD patients needed RRT during follow-up. Kaplan–Meier analysis showed that patients with high ApoB were significantly more likely to progress to RRT than those with low ApoB (log-rank = 16.62, p < 0.001). The presence of high ApoB increased the risk of RRT. Analysis of ApoB as either a categorical (<1.1 g/L or ≥1.1 g/l) or continuous variable by univariate and multivariate regression found that ApoB was an independent risk factor of DKD progression to RRT in this group of DKD patients with stage 3–5 CKD (p < 0.05). Conclusion Increased ApoB was an independent predictor of progression to RRT. A larger study is needed to confirm the unfavorable prognosis of increased ApoB in DKD patients.